Coursework in Australian Doctoral Education. What's Happening, Why and Future Directions? - Kiley, Margaret (Office for Learning and Teaching, 2014)
Over the past 12-18 months several Australian universities have been working with the idea of introducing formal coursework into the PhD. The provision of coursework in PhD programs is common-place in the United States, Canada and Europe, however until recently, there has been little in the way of coursework in the Australian PhD. What Australia does have is a range of Professional Doctorates which generally include 12 months (FTE) of coursework although this varies across institutions and disciplines. The introduction of coursework into the Australian PhD is a development that is being undertaken in the absence of a set of pedagogical, curriculum, organisational and funding principles suited to the Australian context and the context of specific PhDs programs that can be used as a basis for development of such programs. Therefore, this project examined the issues that are deemed necessary for the possible implementation of formal coursework in the Australian PhD in its many and varied forms. This document is the final report from the project.